Targeting the Antibody Checkpoints to Enhance Cancer Immunotherapy–Focus on FcγRIIB - Teige, Ingrid; Mårtensson, Linda; Frendéus, Björn L. (Frontiers in Immunology, 2019)
Immunotherapy with therapeutic antibodies has increased survival for patients with hematologic and solid cancers. Still, a significant fraction of patients fails to respond to therapy or acquire resistance. Understanding and overcoming mechanisms of resistance to antibody drugs, and in particular those common to antibody drugs as a class, is therefore highly warranted and holds promise to improve response rates, duration of response and potentially overall survival. Activating and inhibitory Fc gamma receptors (FcγR) are known to coordinately regulate therapeutic activity of tumor direct-targeting antibodies. Similar, but also divergent, roles for FcγRs in controlling efficacy of immune modulatory antibodies e.g. checkpoint inhibitors have been indicated from mouse studies, and were recently implicated in contributing to efficacy in the human clinical setting. Here we discuss evidence and mechanisms by which Fc gamma receptors - the “antibody checkpoints” - regulate antibody-induced antitumor immunity. We further discuss how targeted blockade of the sole known inhibitory antibody checkpoint FcγRIIB may help overcome resistance and boost activity of clinically validated and emerging antibodies in cancer immunotherapy.